POST-METAPHYSICS AND THE PARADOXICAL TEACHINGS OF JESUS. - Dierkes, Christopher (Journal of Integral Theory & Practice)
The article reviews the book "Post-Metaphysics and the Paradoxical Teachings of Jesus: The Structure of the Real," by Cameron Freeman.